Cultural Literacy and Citizenship Based in Elementary Schools - Maqfira (International Journal of Students Education, 2024)
Cultural and civic literacy is an important aspect of education in elementary schools. Aims to analyze different approaches in developing cultural and civic literacy in elementary schools. The cultural and primary literacy levels of this research. Various literature studies show that students have difficulty understanding cultural values and the concept of citizenship. Lack of exposure to local wisdom, limited integration of local wisdom in the curriculum, and focus on academic achievement are the main challenges. This research uses a qualitative descriptive approach by analyzing data from field observations, interviews with teachers and students, as well as documentation studies explaining the importance of learning and applying it in the learning process. This research is qualitative with a literature study approach, using books and literature as the main sources. This research is expected to contribute to increasing cultural and civic literacy, forming a young generation who understands culture, citizenship and the values that underlie national and state life.